Effects of different serotonin receptor subtype antagonists on the development of cardiac allograft vasculopathy in murine aortic allografts - Gocht, Annika; Distler, Jörg; Spriewald, Bernd; Ramsperger-Gleixner, Martina; Weyand, Michael; Ensminger, Stephan M.; Heim, Christian (Transplant Immunology, 2018)
BACKGROUND: Cardiac allograft vasculopathy (CAV) is the main obstacle for long-term survival after heart transplantation. Alloimmune mediated chronic vascular rejection results in several mechanisms like platelet activation, immigration of inflammatory cells through the endothelial layer and proliferation and migration of smooth muscle cells (SMCs). Serotonin (5-HT) promotes these processes via activation of 5-HT2 receptors. We hypothesized that inhibiting 5-HT2 receptors ameliorates the development of CAV. METHODS: CBA/JRj mice recieved aortic grafts from C57BL/6 mice. After transplantation until recovery of organs, recipients were treated with serotonin receptor antagonists: sarpogrelate (5-HT2A), SB 204741 (5-HT2B) or terguride (5-HT2A+B). Mice were sacrificed after 14 days for qRT-PCR analysis or after 30 days for histological evaluation. Serum serotonin ELISA was done at both time points. RESULTS: Elevated serum serotonin levels were significantly reduced after 5-HT2A antagonist treatment as was 5-HT2A receptor expression. This went along with reduced inflammation characterized by significantly fewer infiltrating macrophages and pro-inflammatory intragraft cytokines and with reduced tissue remodeling evident as significantly less neointima formation. CONCLUSION: Inhibition of the 5HT/5-HT2A receptor axis leads to significantly reduced neointima proliferation after aortic transplantation associated with reduced transendothelial migration of macrophages and decreased expression of inflammatory cytokines. These findings have translational implications as inhibitors of 5HT2A like sarpogrelate are already approved for clinical use.
EVALuna2:35106